Blank canvas or under construction? Examining the pre-academy experiences of young developing professional team sports athletes - Papastaikoudis, F.; Collins, R.; Collins, D. (Frontiers in Sports and Active Living, 2023)
Introduction: Extensive research has been carried out on Talent Development (TD) environments and an increasing amount of work shows the development of psychological characteristics as an important formal part of the academy experience. Importantly, however, very little attention has been paid to what types of skills, if any, young players arrive with. In other words, there seems to be an assumption that young athletes arrive at the academy as a blank canvas.